2015
DOI: 10.1097/bsd.0000000000000041
|View full text |Cite|
|
Sign up to set email alerts
|

Preoperative Risk Factors for Recurrent Lumbar Disk Herniation in L5–S1

Abstract: Moderate disk degeneration, a large sROM, a small RT, and a low IHI are biomechanical risk factors of rLDH in L5-S1. The results also suggested being male and having a large annular defect increase recurrence after discectomy, especially in cases of ipsilateral rLDH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
82
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 18 publications
8
82
1
6
Order By: Relevance
“…Kim et al 13,14 found significant association between an increased disc height index and sagittal range of motion at the operated level, to a higher rate of recurrence. Clearly, causes for a recurrent disc can be multifactorial.…”
Section: Risk Factorsmentioning
confidence: 97%
“…Kim et al 13,14 found significant association between an increased disc height index and sagittal range of motion at the operated level, to a higher rate of recurrence. Clearly, causes for a recurrent disc can be multifactorial.…”
Section: Risk Factorsmentioning
confidence: 97%
“…In 2006, Carragee et al reported an 18% re-herniation rate after limited discectomy, compared to 9% after aggressive procedures [18]. Some studies also reported a much higher incidence of symptomatic recurrent LDH to about 18%-27.3% in patients with large annular defects (> 6 mm) [19][20][21]. Thus, attempts to reduce the recurrent herniation have been tried again and again, and annular repair may be an answer.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors are affecting the recurrence of LDH, such as postoperative defect of the annulus fibrosus, the degree of disc degeneration, obesity, smoking, and other factors. 4,7,[21][22][23][24][25] Lebow et al found that recurrence after nucleus pulposus removal occurred mostly in the original nucleus. 26 Rupture of AF around with high level of phospholipase A 2 , which aggravates the hyperplasia of scar tissue.…”
Section: Discussionmentioning
confidence: 99%